Effect of Elagolix in comparison to Dienogest in the treatment of symptomatic adenomyosis - Jubaida, Umme; Deeba, Farzana; Ishrat, Shakeela; Anwary, Shaheen Ara; Sultana, Rebeka; Alamgir, Chowdhury Faisal; Darmini, Maliha; Banu, Jesmine (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Adenomyosis, a benign gynecological disorder, is diagnosed with increasing frequency in infertile patients since women delay their first pregnancy. Common symptoms of adenomyosis are dysmenorrhea and heavy menstrual bleeding (HMB), resulting in poor quality of life. Elagolix, the oral GnRH antagonist, acts by reducing the occurrence of ectopic endometrial implants in the myometrium. It diminishes uterine volume, reduces dysmenorrhea and heavy bleeding, and improves fertility outcomes. Dienogest, a synthetic oral progestin highly selective for progesterone receptors, reduces the painful symptoms in women with adenomyosis. The aim or this study was to compare the effect of Elagolix with Dienogest in the treatment of symptomatic adenomyosis. Methods: This randomized controlled trial was conducted in the department of reproductive endocrinology and infertility, Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, from January 2024 to December 2024. A total of 58 participants with symptomatic adenomyosis were randomly assigned to 2 groups (n=29). Each group received either Elagolix (200 mg) or Dienogest (2 mg) once daily for 3 months. Results: Compared between the two groups, post-treatment mean changes of VAS score (6.25±1.83 vs 4.84±1.56), hemoglobin (-1.21±0.97 vs-0.20±0.56), and median uterine volume (5.1 vs 1.2) were significantly higher in the Elagolix group than the Dienogest group. HMB was also significantly reduced (3.7% vs 23.1%) in the Elagolix than the Dienogest group after 3 months of treatment. Conclusion: Elagolix significantly reduced VAS score, HMB, and uterine volume in symptomatic adenomyosis compared to Dienogest.